Exploring the Synergies of Single-Molecule Fluorescence and 2D Materials Coupled by DNA - Richter, Lars (2023)
The world of 2D materials is steadily growing, with numerous researchers attempting to discover, elucidate, and exploit their properties. Approaches relying on the detection of single fluorescent molecules offer a set of advantages, for instance, high sensitivity and specificity, that allow the drawing of conclusions with unprecedented precision. Herein, it is argued how the study of 2D materials benefits from fluorescence-based single-molecule modalities, and vice versa. A special focus is placed on DNA, serving as a versatile adaptor when anchoring single dye molecules to 2D materials. The existing literature on the fruitful combination of the two fields is reviewed, and an outlook on the additional synergies that can be created between them provided.